Micro mechanics of drained and undrained shearing of compacted and overconsolidated crushable sand - de Bono, John P.; McDowell, Glenn R. (Thomas Telford ICE Publishing, 2018)
A numerical crushable soil sample has been created using the previously published McDowell and de Bono (2013) model and subjected to a range of stress paths. Compacted sand simulations are performed using conventional triaxial stress paths, constant mean stress and constant volume conditions and a critical state line established. Overconsolidated samples have been created by crushing the soil down the isotropic normal compression line, unloading, and shearing at constant radial stress, constant mean stress or constant volume and a critical state line is again established. The critical state line is unique at high stresses for the simulated compacted and overconsolidated sands and is parallel to the isotropic normal compression line, in agreement with available data and a previously published theory. The critical state line at low stress levels is non-unique and a function of the particle size distribution, in agreement with available data. Constant volume tests exhibit the well-known phenomena of phase transformation points and peak strengths are observed for ‘drained’ soils on the dense side of critical. The numerical soil produces a state boundary surface that compares well to available data.